Association between CRP Level on Admission Day and Length of Hospitalization and Engraftment in Patients Undergoing Autologous Hematopoietic Stem Cell Transplantation - Farzaneh Tavakoli; Elham Roshandel; Hossein Bonakchi; Abbas Hajifathali; Sayeh Parkhideh (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Several studies investigated the role of C-reactive protein (CRP) during transplantation and inflammation, and clinical outcomes after stem cell transplantation. In this study, we examined the relationship between the earliest CRP level on admission day, and the first outcome after transplantation, myeloid and platelet engraftment, and the length of hospitalization in patients with Autologous hematopoietic stem cell transplantation (Auto-HSCT). Materials and methods: In this retrospective study, using clinical records from 2014-2020, information including patients’ demographic characteristics, CRP levels on admission day, white blood cell, and platelet counts were investigated. Engraftment day and duration of hospitalization were also recorded. To analyze the data, Cox regression, score process plot, Kolmogorov-type supremum test, and linear regression were performed. Results: Results did not show a significant relationship between CRP level on first day of hospitalization, the day of myeloid and platelet engraftment, and duration of hospitalization (P values= 0.91, 0.68, 0.39 respectively). Conclusion: Future studies, assessing changes in CRP levels, along with the impact of other inflammatory factors during conditioning chemotherapy or the day of stem cell injection, might improve our understanding of lymphoma and multiple myeloma treatment and management.